[4 + 2]-Cycloaddition with Inverse Electron Demand: Reaction of 3-Vinylindoles with Dimethyl 1,2,4,5-Tetrazine-3,6- dicarboxylate - Ulf Pindur; Ludwig Pfeuffer (CHIMIA)
The 1'-substituted 3-vinylindoles 1a and 1b react locoselectively with the tetrazine 2 to form the corresponding 1,4-dihydro-1,2-diazines. The 2'-methoxy-substituted compound 1c yields the 4-(indol-3-yl)-substituted 1,2-diazine 5 on reaction with the tetrazine 2. The reactions proceed through [4 + 2]-cycloaddition, [4 + 2]-cycloreversion, and, in the case of the reaction of 1c, an additional elimination of methanol.